Pengaruh Natrium Tripolyphospate (Na5p3o10) Terhadap Sifat Mekanik Beton Pada Pengecoran Dalam Air Berlumpur - Maharani Rahma Annisya; Ismeddiyanto Ismeddiyanto; Andre Novan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
In construction work certain conditions where forced by a concrete structure must be moulded directly in water into consideration for casting on location. The condition of casting work in water does not only occur in environments where there is normal water but also in environments that have sludge levels. The use of Tripolyphosphate Sodium is expected to be able to become a mixture in casting concrete in water without conventional compaction so that the concrete mixture is able to flow and solid itself properly. This study examines the effect of Sodium Tripolyphosphate as a constituent in concrete mixes on the mechanical properties of concrete including compressive strength and tensile strength in casting in water, especially in muddy water environments. The study was conducted experimentally with a cement water factor value of 0.37, a percentage of Sodium Tripolyphosphate 10% by weight of cement and a percentage of rock ash 15% by weight of fine aggregate. Concrete compressive strength test was carried out on 6 cylinders 28 days old with a diameter of 10 cm x height 20 cm and for tensile tensile strength testing was also carried out on 6 cylinders 28 days old with a diameter of 15cm x height 30 cm. Based on the results of the compressive strength test of concrete at 28 days, the average compressive strength of concrete for direct castings in normal water is 12,14 MPa, while for the average compressive strength for concrete casted directly in muddy water is 9,49 MPa. So that the compressive strength of concrete, which is cast directly in muddy water has decreased compressive strength by 21.82% of concrete in normal water. For the results of the average split tensile strength of 28 days old concrete, obtained in concrete that is cast directly in ordinary water conditions is 1.37 MPa, while for the average split tensile strength in concrete by direct casting in water conditions muddy at 1.11 MPa. Keywords : Sodium Tripolyphospate, Muddy Water Environment, Compressive Strength, Tensile Strength.